2016
DOI: 10.2174/1874325001610010862
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Regenerative Medicine Strategies that Utilize Nanotechnology to Treat Cartilage Damage

Abstract: Background:Cartilage is an important tissue found in a variety of anatomical locations. Damage to cartilage is particularly detrimental, owing to its intrinsically poor healing capacity. Current reconstructive options for cartilage repair are limited, and alternative approaches are required. Biomaterial science and Tissue engineering are multidisciplinary areas of research that integrate biological and engineering principles for the purpose of restoring premorbid tissue function. Biomaterial science traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 92 publications
(118 reference statements)
0
14
0
Order By: Relevance
“…1). 17 The two main constituents of the tissues in the human body are cells and extracellular matrix (ECM). Cells regulate body processes performing normal maintenance and wound healing, meanwhile ECM components, composed of a dynamic arrangement of polysaccharides and proteins (collagen, elastin, fibrinogen, silk fibroin, elastin, keratin, etc.…”
Section: Tissue Engineering General Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 17 The two main constituents of the tissues in the human body are cells and extracellular matrix (ECM). Cells regulate body processes performing normal maintenance and wound healing, meanwhile ECM components, composed of a dynamic arrangement of polysaccharides and proteins (collagen, elastin, fibrinogen, silk fibroin, elastin, keratin, etc.…”
Section: Tissue Engineering General Aspectsmentioning
confidence: 99%
“…Biodegradability is an essential demand since matrices should ideally be absorbed by the nearby tissues without the need of surgical displacement; as a consequence, the rate at which degradation takes place has to occur simultaneously with the rate of tissue evolution. 19 Figure 1: Basic principles of tissue engineering (reprinted with permission from R. Kumar et al, 17 Copyright © 2016, Bentham Science Publishers)…”
Section: Tissue Engineering General Aspectsmentioning
confidence: 99%
“…Cartilage is an avascular tissue composed of chondrocytes entrapped in an extracellular matrix (ECM) rich in proteoglycans and collagens; therefore, current reconstructive options for cartilage repair are limited (Swieszkowski et al, 2007;Kumar et al, 2016). Tissue engineering strategies have been based mostly on matrix seeded with either chondrocytes or MSCs (Li et al, 2005).…”
Section: Cartilage Regenerationmentioning
confidence: 99%
“…Presently two classes of prosthesis are in use, mainly autologous graft and biomaterials 12 . In this regard using autografts has some disadvantages like acquiring microbes on their surfaces, donor site morbidity, possibility of displacements but compared to autografts, biomaterial application as replacement purpose is considered as an ideal option at the present time 13 . Currently biomaterial‐related infections are a crucial problem and to overcome that biomaterial possessing‐reduced bacterial adherence is the major concern in biomaterial industry 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Silicone implants already have been successfully used in rhinoplasty 18,19 . Previous studies have revealed that silicone implants have also been applied in jaw surgery which was proposed in 1963 20 and in reconstruction of middle‐ear in which success rate was 80% 13 . Using silicones in developing implants has some short comings such as fast degradation due to temperature and humidity changes, tissue puckering as well as deposition of microscopic residues in porosities on the material surface 21 .…”
Section: Introductionmentioning
confidence: 99%